2017
DOI: 10.1292/jvms.17-0340
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Klotho protein and Klotho mRNA expression in a hydroxy-L-proline induced hyperoxaluric rat model

Abstract: Klotho protein is recognized as having a renoprotective effect and is used as a biomarker for kidney injury. We investigated the level of Klotho protein in hyperoxaluria-induced kidney injury and the effects of vitamin E (Vit E) and vitamin C (Vit C) supplementation. Hyperoxaluria was induced by feeding 2% (w/v) Hydroxy-L-proline (HLP) in the drinking water for 21 days. Rats were divided into 5 groups; control (Group 1, n=7), HLP treated rats that received nothing else (Group 2, n=7), Vit E (Group 3, n=6), Vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
4
2
Order By: Relevance
“…Interestingly, there are investigations demonstrating Klotho deficiency as a biomarker for kidney injury and for number of cancers, including breast cancer, lung cancer or hepatocellular carcinoma. They showed decrease in both plasma and urine Klotho protein levels in animal kidney injury models 34,39,44 . However, in our investigation, ischaemic heart injury and reduced mechanical function of the heart were related to the high content of Klotho in coronary effluents.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…Interestingly, there are investigations demonstrating Klotho deficiency as a biomarker for kidney injury and for number of cancers, including breast cancer, lung cancer or hepatocellular carcinoma. They showed decrease in both plasma and urine Klotho protein levels in animal kidney injury models 34,39,44 . However, in our investigation, ischaemic heart injury and reduced mechanical function of the heart were related to the high content of Klotho in coronary effluents.…”
Section: Discussioncontrasting
confidence: 52%
“…They showed decrease in both plasma and urine Klotho protein levels in animal kidney injury models. 34,39,44 However, in our investigation, ischaemic heart injury Research from the last few years showed protective effect of Klotho overexpression or administration during ischaemic injury of the brain and kidneys. 13,34 Thus, we studied if Klotho administration may mitigate I/R injury also in the cardiac cells.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…We hypothesize that several mechanisms may underlie these observed relationships. Dietary carbohydrates themselves can serve as a source of certain vitamins [ 33 , 34 ], minerals [ 35 ], and fiber [ 27 ], which could positively influence Klotho protein expression. Additionally, low-carbohydrate-intake diets tend to inevitably reduce the intake of high-quality carbohydrates [ 28 , 36 ], including fruits, non-starchy vegetables, and whole grains, and simultaneously alter the amount and type of gut microbiota and affect hepatic FGF21 production [ 20 , 37 ], all of which may downregulate Klotho levels by modulating the levels of inflammation and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%